Cytotoxic Aryltetralin Lignans from Fruits of Cleistanthus indochinensis - Trinh Thi Thanh, Van; Pham, Van Cuong; Doan Thi Mai, Huong; Litaudon, Marc; Guéritte, Françoise; Nguyen, Van Hung; Chau, Van Minh (Planta Medica, 2014)
Eight new aryltetralin lignans, cleisindosides A–F (1–6), picroburseranin (7), and 7-hydroxypicropolygamain (8), were isolated from the fruits of Cleistanthus indochinensis (Euphorbiaceae). The structures of the isolates were established on the basis of their one- and two-dimensional NMR spectral data, as well as their mass spectrometric data. Compound 7 was found to have potent cytotoxicity against oral epidermoid carcinoma cells with an IC50 value of 0.062 µM, whereas glycosylation to 3 (IC50 7.5 µM) and stereochemical changes to 8 (IC50 10.8 µM) led to marked decreases in biological activity. Thus, it was determined that the C-7 and C-8′ positions are critical for the biological activity of the lignans from this plant.
Keywords: Euphorbiaceae; Cleistanthus indochinensis; lignans; glycosides; cytotoxicity